دراسة تأثير العوامل الاستثمارية على التلوث الناتج عن عمل محركات الديزل (Latakia University Journal -Engineering Sciences Series, 2019)
إن زيادة استخدام محركات الديزل على وسائل النقل وتشديد القيود الموضوعة على تلوث البيئة يستدعي البحث في طرق تخفيف التلوث الناتج عن عمل تلك المحركات. يستعرض هذا البحث ومن خلال تجارب أجريت على محركات الديزل تأثير العوامل الاستثمارية في التلوث الناتج عن محركات الديزل ومنها السرعة ، الحمولة ، الحالة الفنية للمحرك وعوامل الوسط المحيط. وقد دلت نتائج التجارب على أنه توجد علاقة معقدة بين ظروف عمل المحرك وتشكل المركبات الملوثة في غازات الاحتراق مما يتطلب تزويد محركات الديزل بأنظمة تحكم أوتوماتيكية توفر إمكانية التحكم الدقيق بعمليات حقن الوقود وشحن الهواء والتبادل الغازي وتدوير غازات العادم إضافة إلى ضرورة المراقبة والحفاظ الدائم على الأوضاع العيارية المثالية الموصى بها للمحركات من قبل الشركات الصانعة . The increase use of the diesel engines and the hard conditions of the transportation regulation on the environmental pollution, need some Kind of research to decrease the pollution percentage produced by Those engines. This work gives some experiments on the work of Those engines and its effects on the pollution function produced by if, such as speed, Loads, technical states of it and the environmental media. We proved that there is a complex-relation between the engines-work-condition And the pollution formation products by the engines gases. This requires the use of special automatic control systems for accurate fuel injections and supercharge . This allows a gas exchange and exhaust gases-recirculation, and gives use an optimal and standard conditions of the engines use.